Atención al usuario y su influencia en la imagen institucional del área administrativa de la facultad de filosofía letras y ciencias de la educación, universidad de Guayaquil, periodo 2015-2016 - Chóez Beltrán, Johanna Elizabeth (2015)
This project was carried out with the aim to implement a working tool that helps the administrative staff of the Faculty of Philosophy at the University of Guayaquil to improve and enhance their profile in the service user. The Faculty of Philosophy, is an institution with a historical trajectory, training of professionals in different fields of education; since in the country, it is the pioneer institution and project manager directing the educational process of the students, who are the users, who will engage in this investigation……